Biodiesel production via homogeneous lewis acid catalyzed transesterification - Abd Rahman, Diyanti (2010)
The transesterification of triglyceride mostly found in vegetable oils with methanol using homogeneous lewis acid is one of promising method to convert triglyceride into fatty acid methyl ester which is an alternative to replace fossil fuel as energy source mostly in transportation industry. This study aimed to determine the conversion of fatty acid methyl ester and also to determine the optimum conditions for the production of methyl ester via transesterification process using aluminium chloride as the catalyst and methanol as solvent. By using conventional catalyst such as NaOH and KOH, it formed soap via saponification process and produce huge amount of wastewater in order to separate the reactant and product. Scopes for this research including the effect of molar ratio methanol to oil, effect of reaction temperature and effect of catalyst concentration. After experiments have been done, the most optimum conditions for sunflower oil transesterification can be achived at reaction temperature is 100°C, molar ratio 12:1 methanol to oil and 5 g of aluminium chloride. The highest conversion from these conditions is 91% conversion of fatty acid methyl ester.